Nature and effects of cattle rustling on rural community well-being in Kaduna State, Nigeria - Bashir, Abubakar Mohammed (2019)
Despite the role of the government to improve the well-being of its citizenry, there are agitations from many quarters on the deteriorating nature of their well-being due to cattle rustlers’ activities in Kaduna State, Nigeria. Cattle rustlers’ continuous activities had become an existential threat in the State and significantly affected the people’s well-being, particularly in rural populace. Thus, this study aims to investigate the nature of cattle rustling within the rural populace of Kaduna State and its effects on their well-being, as well as analyzing preventive measures taken by them against cattle rustling. Eco-violence theory, Queer Ladder theory of mobility, and Securitization theory have been selected and utilized in this study. This study adopts qualitative research methods by conducting in-depth interviews, focus group discussion (FGD) and observation for data collection. Three local government areas are purposively selected with twenty (20) respondents are selected for IDI using snowballing sampling method. Two FGD sessions are also conducted with a group of herdsmen and farmers, while relevant facilities are thoroughly observed. Four themes have later been developed and thematic data analysis has been completed by using Nnvivo 11. The result shows that violent conflicts between herdsmen and farmers occurred in the study area. The findings reveal that cattle rustling always involved specific group like an organized crime, which mostly occurred at night and dominated by aggressive herdsmen youths. The study also discovers that cattle rustling has significantly affected the economy, education, health, lives, property, and psychology of the rural populace. This study divulges that few preventive approaches like border security, disarmament, security agents and vigilante groups have been initiated in Kaduna State. However, those approaches seem ineffective to deal with cattle rustling activities there. Therefore, this study recommends that the securitization of cattle rustling, rural community policing have to be improved alongside with the improvement on the facilities and activities of security agents.